Fetal case of rare association of hypoplastic left heart syndrome and absent atrial septum accompanied by mixed form of supracardiac total anomalous pulmonary venous connection. Issue 2 (6th January 2022) - Maruyama, Wakako; Kawasaki, Yuki; Murakami, Yosuke; Fujino, Mitsuhiro; Sasaki, Takeshi; Nakamura, Kae; Ehara, Eiji
Abstract: Abnormal pulmonary venous flow patterns on fetal echocardiography and a nutmeg lung pattern on fetal magnetic resonance imaging are seen in patients with pulmonary venous stenosis. The association between these findings and the degree of pulmonary venous stenosis remains unknown. We report an extremely rare case of a fetus diagnosed with hypoplastic left heart syndrome complicated by an absent atrial septum and supracardiac total anomalous pulmonary venous connection with left pulmonary venous congestion. This case suggests that compared to non‐pulsatile continuous pulmonary venous flow, the nutmeg lung pattern can only be observed with severe pulmonary congestion and advanced pulmonary lymphangiectasia.